PREFERENSI EKSTRAKURIKULER SISWA DALAM PERSPEKTIF JENIS PERMAINAN - Hetty Dwi Purwaningsih; Sapto Wibowo; Advendi Kristiyandaru (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The selection of extracurricular activities is an important part of the development of students' interests and talents, but the factors that influence these preferences are not fully understood, especially in the context of the tendency of the type of games that students prefer. The type of game, whether physical, strategic, creative, competitive, or collaborative, is considered to reflect the student's behavioral tendencies, learning styles, and natural interest in certain activities. This study aims to identify the relationship between the types of games that students like and the extracurricular choices they take at school. The research uses a quantitative approach with a survey design. The research sample consisted of 109 students of SMP Negeri 1 Porong who were selected through purposive sampling techniques. The instrument is in the form of a Likert scale questionnaire that measures the tendency of the type of game and the extracurricular preferences of students. Data were analyzed using descriptive statistics, correlation tests, and tendency analysis to map the patterns of relationships between variables. The results of the study are known that the average value (mean) of student interest is 58.29 with a standard deviation of 7.85. A median score of 59 indicates that most students have a level of interest that is close to the group average. A minimum score of 28 and a maximum of 75 showed a fairly wide range of variation between respondents, indicating that the tendency of physical games, such as outdoor and competitive games, was strongly correlated with sports extracurricular choices. Meanwhile, students who like strategic games and logic tend to choose academic extracurriculars and science clubs. Students who have an interest in creative and collaborative play are more likely to choose arts, language, and organizational extracurriculars. These findings confirm that the type of game is a potential indicator in understanding the orientation of students' interest in extracurricular activities. In conclusion, the tendency of the type of play can be the basis for schools to design extracurricular programs that are more relevant to the characteristics of the students. This understanding can help teachers and school managers in providing more targeted guidance and creating a learning environment that is more supportive of the development of students' interests and potential. Topics: Student perspective, extracurriculars, types of games